Material didáctico impreso "MY CLASSROOM" y su influencia en la comprensión de textos escritos en inglés, en el área de idioma extranjero, de los estudiantes del 3° grado de educación secundaria de la l.E. "Santa Rosa" de la ciudad de Tarapoto, en el año 2008 - Del Aguila Torres, Carol (2008)
lt is known that in most of the Educational lnstitutions of San Martin County and Region is exactly the teachers use strange methods and they lack authentic educational material to use far the application of the method in English teaching language, even though we live the computer science and the cybernetics current time. Likewise, in the 72 educational centers of high school that they are in San Martin ~ County, they use the active methods to teach this language at the present time whose origin is external to us, where the students build their knowledge up based on their own experiences. Owing to this fact, the students of San Martin County and Region Educational lnstitutions, Tarapoto district, they are harmed, because it is not used a certainly didactic material far English teaching language, for that reason the learning is poorly; on the other hand, the English classes are given by teachers, most of them are discouraging and this is the reason for students don't pass the subject with a low grade. Besides being given the case that students repeat the year, it would be an additional expense, not only far family parents, but also for the state and the small town. With the intention of contributing to solution of this problem, we carried out the research that it had as aim: Demonstrating the influence of the Printed Didactic Material "My Classroom" in order to improve the English written texts comprehension with students of the Third Year at the Educational lnstitution "Santa Rosa" high school of Tarapoto city, by the year 2008. In order to be able to get the proposed aim, it has been guided to validate the following hypothesis: lf the Printed Didactic Material, "My Classroom", is applied, it will increase the learning of the English written texts comprehension then, with students of the Third Year at the Educational lnstitution "Santa Rosa" high school of Tarapoto city, by the year 2008. In order to contrast the hypothesis, we carried out an applied research, with experimental level, with pretest and post test quasi experimental design with control group. The sample was made up by 59 students of the Third Year at the Educational lnstitution "Santa Rosa" high school,_ 29 of which were made up by the experimental group and 30 the control group, who were given an objective test before and after the experiment. The analysis of the data in the post •test with the experimental and control group, by means of the normal distribution in z, it has allowed to check out the hypothesis, such it is the case that Zc equals 10,35 is greater than Zt equals 1,64; then Zc being located in the rejection zone, it shows that ít has allowed to conclude that if the Printed Didactic Material, "My Classroom", is applied, it increases the learning of the English written texts comprehension then, with students of the Third Year at the Educational lnstitution "Santa Rosa" high school of Tarapoto city, by the year 2008.